Secrecy, State-Private Networks and Operational Effectiveness in Cold War Europe. (15th June 2016) - PULLIN, ERIC
Abstract : Secrecy has unintended consequences. The release on 9 December 2014 of the US Senate Intelligence Committee's report on the torture of terrorism detainees focused public attention on the secret activities of the Central Intelligence Agency (CIA). Regrettably, lost amidst debate over justifying or condemning state-sponsored torture is a more basic concern, the issue of state secrecy, which underlies the discussion of how governments promote national ends. Only two days after the issuance of the Senate Intelligence Committee's report, the US House of Representatives adjourned without taking action on the Freedom of Information Act reform bill – despite receiving unanimous approval in both houses. This bill would not have required complete openness, but it would have eliminated many of the arbitrary mechanisms that enable the CIA and other governmental agencies to suppress requests for information. Although the House Republican leadership failed to put the act on the legislative calendar, the Obama administration's Department of Justice also deserves opprobrium for surreptitiously opposing the act behind the scenes. The US government's disregard for establishing reasonable rules of transparency virtually guarantees that the CIA will continue to suppress its records, and thus public scrutiny of its unchecked activities, for a very long time to come.